Combined use of serum MCP-1/IL-10 ratio and uterine artery Doppler index significantly improves the prediction of preeclampsia - Cui, Shihong; Gao, Yanan; Zhang, Linlin; Wang, Yuan; Zhang, Lindong; Liu, Pingping; Liu, Ling; Chen, Juan (Clinica chimica acta, 2017)
Background: Monocyte chemotactic protein-1 (MCP-1, or CCL2) is a member of the chemokine subfamily involved in recruitment of monocytes in inflammatory tissues. IL-10 is a key regulator for maintaining the balance of anti-inflammatory and pro-inflammatory milieu at the feto-maternal interface. Doppler examination has been routinely performed for the monitoring and management of preeclampsia patients. This study evaluates the efficiency of these factors alone, or in combination, for the predication of preeclampsia. Methods: The serum levels of MCP-1 and IL-10 in 78 preeclampsia patients and 143 age-matched normal controls were measured. The Doppler ultrasonography was performed and Artery Pulsatility Index (PI) and Resistance Index (RI) were calculated for the same subjects. Results: It was found that while the second-trimester serum MCP-1, IL-10, MCP-1/IL-10 ratio, PI, and RI showed some power in predicting preeclampsia, the combination of MCP-1/IL-10 and PI and RI accomplishes the highest efficiency, achieving an AUC of 0.973 (95% CI, 0.000–1.000, P<0.001), a sensitivity of 94%, and a specificity of 80%. Conclusions: The use of MCP-1/IL-10 ratio in combination with ultrasound findings appears to provide a promising modality for predicting preeclampsia. Future studies using a larger sample can be conducted to construct an algorithm capable of quantitative assessment on the risk of preeclampsia. •The use of MCP-1/IL-10 ratio in combination with ultrasound findings appears to provide a promising modality for predicting preeclampsia.•Future studies using a larger sample can be conducted to construct an algorithm capable of quantitative assessment on the risk of preeclampsia.•The most valuable finding of this study is the much-improved performance by a combined use of MCP-1/IL-10 and the Doppler ultrasound Index.